Comparison of Clinical Outcomes of Patients With Chronic Vein Insufficiency Underwent Endovenous Laser Ablation With Puncture Above The Knee And Below The Knee Techniques Based on Venous Clinical Severity Score And Venous Disability Score Assessment - Suprayoga, Imam Mi'raj; Kurnianingsih, Novi; Sargowo, Djanggan (Universitas Brawijaya, 2024)
Background: In chronic venous insufficiency (CVI), a puncture below the knee is done to access the great saphenous vein for endovenous laser ablation (EVLA). Getting a puncture below the knee is difficult in some conditions. Puncture above the knee to access the incompetent saphenous vein is another option.Â Objective: This study compared CVI patients' clinical results after EVLA with above- and below-the-knee punctures.Methods/Design: This retrospective, single-centre cohort study compared clinical outcomes after two EVLA technical punctures. Puncturing the GSV below the knee was one way. An above-knee GSV puncture was chosen as an alternative. At all follow-up visits, clinical outcomes, closure rate, and complications such as thrombosis, bruising, burn damage, and paresthesia were assessed.Â Â Results: This study has recruited 248 patients, with 132 patients in the below-knee group and 116 patients in the above-knee group. Similar clinical outcomes after the procedure with the Venous Clinical Severity Score (VCSS) were seen in both groups (p = 0.875) and with the Venous Disability Score (VDS) were seen in both groups (p = 0.777) without significant difference. The closure rate in both groups was 100%. Complications, including thrombosis, did not show statistical significance between groups (p = 1.000). Bruising, burn injuries, and paresthesia were absent in both groups.Conclusion: The EVLA for incompetence GSV using an above-knee puncture was safe and effective and should be considered as an alternative method if the below-knee puncture fails.